THE INFLUENCE OF SEDIMENT GRAIN SIZE AND COMPOSITION ON THE MORPHODYNAMIC STATE OF MIXED SILICICLASTIC AND BIOCLASTIC SAND BEACHES IN ESPIRITO SANTO STATE, BRAZIL - Albino, Jacqueline; Suguio, Kenitiro (Revista Brasileira de Geomorfologia, 2011)
The beaches in front of the Barreiras Formation active sea cliffs are composed of mixed sands, which composition makes it more difficult to interpret the processes of their sedimentation. The most important source of bioclastic particles is calcium carbonate secreting marine organisms, which cover the inner continental shelf bottom abrasion terrace and are eroded by waves. The particles are mostly composed of coralline algae and mollusk shell fragments. The wave energy is dissipated by the presence of abrasion terraces on the inner continental shelf and in the adjacent foreshore zone. Consequently, the beaches acquire dissipative and intermediate stages according Wright et al. (1979) classification. The observed and predicted beach states sometimes showed lack of agreement, the disagreement being due to the geological control in geomorphology and the supply of sediment, i.e. the arrangements of the foreshore terraces and the diversity of mixed sand grain sizes on the beaches, which diversity is produced by very peculiar hydrodynamic processes in which tidal levels and the grain size and composition of sand are fundamental.